Does the Approximate Number System Serve as a Foundation for Symbolic Mathematics?. Issue 2 (3rd April 2017) - Szkudlarek, Emily; Brannon, Elizabeth M.
ABSTRACT: In this article we first review evidence for the approximate number system (ANS), an evolutionarily ancient and developmentally conservative cognitive mechanism for representing number without language. We then critically review five different lines of support for the proposal that symbolic representations of number build upon the ANS, and discuss potential causes of conflicting findings in the literature. Finally, we consider potential mechanisms that could drive a relationship between the ANS and symbolic math. We conclude that while there is considerable evidence the relationship between the ANS and symbolic math is meaningful, we are far from understanding the cognitive and neural mechanisms that underlie this relationship.